Formation evaluation and reservoir characterization of hydrocarbon sand units in “X Field” Onshore Niger Delta Basin (Journal of Pure and Applied Sciences (Science Forum), 2025)
This study investigates the hydrocarbon potential and reservoir quality of sand units within the “X” Field, located onshore in the Niger Delta Basin, through the integrated analysis of wireline log data and core samples. Composite log suites—including gamma ray, resistivity, neutron, density, and sonic logs—from three representative wells were interpreted to evaluate subsurface lithology, fluid types, and key petrophysical parameters relevant to hydrocarbon exploration and production. Two principal reservoir units encountered at varying depth intervals across the wells were identified and designated as the E_7000 and F_9000 Sands. Petrophysical evaluation revealed that these units comprise good-quality sandstone reservoirs, with average effective porosity (Øe) values ranging from 10% to 25%, and net-togross (N/G) ratios between 31% and 85%. Crossplot analyses of log-derived data aided in lithology discrimination, effectively separating sand-dominated and shale-dominated intervals, and indicating hydrocarbon saturation—primarily oil and gas—in the reservoir sands. Integration with core data allowed for a more robust lithofacies and depositional environment interpretation, suggesting a transition from shoreface to fluvio-deltaic and submarine depositional systems. Among the identified units, the Sand A interval within the E_7000 Sand exhibited the best reservoir properties, with an average effective porosity of 23% and a netto-gross ratio of 80%, indicating excellent reservoir potential. The study further observed a general decline in reservoir quality with increasing depth, attributed to enhanced compaction, cementation, and heterogeneity within deeper stratigraphic intervals—common characteristics of deeper sections of the Niger Delta Basin. These findings underscore the importance of integrating core and wireline log data for accurate reservoir characterization, and they provide critical insights for optimizing field development and hydrocarbon recovery in the region.